Algal-bacterial aerobic granule based continuous-flow reactor with effluent recirculation instead of air bubbling: Stability and energy consumption analysis. (September 2019) - Ahmad, Johan Syafri Mahathir; Zhao, Ziwen; Zhang, Zhenya; Shimizu, Kazuya; Utsumi, Motoo; Lei, Zhongfang; Lee, Duu-Jong; Tay, Joo Hwa
Abstract: Algal-bacterial aerobic granular sludge (AGS) based continuous-flow reactors (CFRs) were examined with effluent recirculation instead of air bubbling usually used for AGS cultivation and application. Under effluent recirculation, algal-bacterial AGS exhibited better overall performance and stability over bacterial AGS, achieving averagely dissolved organic carbon (DOC), total nitrogen (TN) and total phosphorus (TP) removals of 40%, 60%, and 15% in comparison to 32%, 35%, and 10% by the bacterial AGS, respectively. More importantly, after being switched from effluent recirculation to intermittent aeration, the algal-bacterial AGS could quickly adapt to the change in operation conditions, clearly indicated by the recovered removals of DOC from averagely 40% to 100%, TN from 60% to 98%, and TP from 15% to 64% along with the improved sludge settleability and stability after 24 day operation. Energy consumption analysis also suggested that algal-bacterial AGS-based CFR systems may have more potentials for energy saving and stable performance under proper operation strategies. Highlights: Algal-bacterial (AB)-AGS was examined in non-aerated continuous flow reactor. AB-AGS removed about 40% DOC, 61% TN and 14% TP, better than AGS in non-aerated CFR. High recirculation deteriorated granular stability rather than removal performance. 100% DOC and 98% TN removals were achieved after intermittent aeration for 24 days. AB-AGS in CFR showed more potentials for energy saving and stable performance.